ORGANOLEPTIC CHARACTERISTICS AND PHYSICAL OF BALINESE PORK FED WITH A MIXTURE OF AMINO ACIDS AND CHOLINE - D. E., Herman; Lindawati, S. A.; Sumadi, I K. (Jurnal Peternakan Tropika, 2024)
This research was conducted to determine the effect of giving a mixture of amino acids (lysine, methionine, tryptophan) and choline vitamins in feed on the physical and organoleptic characteristics of Balinese pork. The research was conducted from September to December 2022 at Batuparas Hamlet, Padangsambian Kaja Village, West Denpasar District, Bali and at the Livestock Products Technology Laboratory, Faculty of Animal Husbandry, Udayana University. The experimental design used in this study was a Complete Randomized Design (RAL) with four treatments and three tests. The four treatments are: P0 uses commercial feed (CP 551 for the starter phase and CP 552 for the grower phase), P1 uses P0 + 5% a mixture of lysine, methionine, tryptophan, and choline from its needs, P2 uses P0 + 10% a mixture of lysine, methionine, tryptophan, and choline from its needs and P3 uses P0 + 15% a mixture of lysine, methionine, tryptophan, and choline from its needs. The results showed that the organoleptic characteristics and physical of balinese pork did not differ markedly (P>0.05) in all treatments. The conclusions of the results of this study showed that the addition of a mixture of amino acids (lysine, methionine, tryptophan) and choline vitamins to the feed did not affect the organoleptic characteristics and physical of balinese pork but the panelists gave a response leading neutral to like.